PRINSIP KEPASTIAN HUKUM YANG BERKEMANFAATAN TERHADAP PENGGUNAAN METERAI ELEKTRONIK DALAM TRANSAKSI DIGITAL DI INDONESIA - Ratnaningsih; Siti Umiyatun Azizah; Bangkit Luhur Prio Wicaksono (LPPM STIH Awang Long, 2026)
Digital transformation has led to the implementation of innovations in stamp duty affixation systems, one of which is the application of barcode-based electronic stamps (e-stamps). This research aims to examine the legal certainty regarding the validity of agreements affixed with e-stamps by referring to the Civil Code (KUH Perdata) and the Law on Electronic Information and Transactions (UU ITE). Using a normative juridical research method, it was found that the use of e-stamps is legally valid as proof of duty payment on documents, even though it's not a condition for the validity of an agreement according to Article 1320 of the Civil Code. E-stamps positively contribute to strengthening the proof of digital agreements, including electronic transactions, accelerating administrative processes, and maintaining document integrity and authentication. However, their implementation still faces obstacles such as a lack of public literacy, limited access to technology, and inconsistent acceptance by several institutions. Therefore, clearer technical regulatory support, increased public understanding, and legal reforms are needed so that e-stamps can fully provide legal certainty in the practice of electronic transactions in Indonesia.